2002
DOI: 10.1111/j.1749-7345.2002.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yellow Lupin Lupinus luteus Meal as an Alternative Protein Resource in Diets for Sea‐Cage Reared Rainbow Trout Oncorhynchus mykiss

Abstract: The performance of sea‐water reared rainbow trout Oncorhynchus mykiss fed three isonitrogenous and iso‐energetic diets based on either fishmeal, solvent‐extracted soybean meal or yellow lupin (L luteus cv. Wodjil) kernel meal was evaluated. Over the course of a 10‐wk study, the fastest growing fish were those fed the diet containing 50% yellow lupin kernel meal (YLM), which grew from 83.6 ± 0.7 g to 322.8 ± 3.2 g (mean ± SEM). This was not significantly faster than growth of fish fed the diet based on 50% solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Based on previously published literature and behavioral observations from the present study, palatability of treatment feeds may have been a factor. During the testing of diets and dietary constituents for various finfish species, a growth response (or lack thereof) is often attributed to palatability (e.g., red drum Sciaenops ocellatus: McGoogan and Gatlin 1997; rainbow trout Oncorhynchus mykiss: Glencross et al 2002;Thiessen and Tyler 2003). Observations from the present study indicated that bonytails fed the two shrimp diets (high and low protein) were more active feeders than fish offered the catfish and trout diets.…”
Section: Discussionmentioning
confidence: 57%
“…Based on previously published literature and behavioral observations from the present study, palatability of treatment feeds may have been a factor. During the testing of diets and dietary constituents for various finfish species, a growth response (or lack thereof) is often attributed to palatability (e.g., red drum Sciaenops ocellatus: McGoogan and Gatlin 1997; rainbow trout Oncorhynchus mykiss: Glencross et al 2002;Thiessen and Tyler 2003). Observations from the present study indicated that bonytails fed the two shrimp diets (high and low protein) were more active feeders than fish offered the catfish and trout diets.…”
Section: Discussionmentioning
confidence: 57%
“…1998) or k E = 0.68 in another study (Rodehutscord & Pfeffer 1999). This higher energy utilization efficiency difference is suggested to be a genetic effect, with faster growth noted previously being from the Pemberton strain of rainbow trout compared with other rainbow trout strains (Glencross et al. 2002; Molony et al.…”
Section: Discussionmentioning
confidence: 67%
“…2007) were suggested to be a possible genetic effect. Faster growth from the Pemberton strain of rainbow trout (Glencross et al. 2002; Molony et al.…”
Section: Discussionmentioning
confidence: 99%